Training Program by Weight to Develop the Muscular Strength of the Upper Limb of the body for Welding Department Students in Jubail Technical institute - Alamri, Khaled Hadi (Journal of Humanities & Social Sciences, 2021)
The study aimed to identify the effectiveness of a training program by Weight to improve the muscular strength of the upper body for the students of the Industrial Welding Department at Jubail Technical Institute. The researcher followed the experimental approach in his study; where the pre- and post-dimensional design of an experimental group consisting of (55) students from the Industrial Welding Department at the institute was used. The study included a training program consisting of (18) units with (24) training hours for a period of (6) weeks. The study concluded that there were statistically significant differences between the pre- and post-measurement among the students in the experimental group from the Industrial Welding Department at Jubail Technical Institute in favor of the post measurement. In light of the results, the study recommends the necessity of paying more attention to the training programs that help to improve the muscular strength in the upper part of the body for the students of the Industrial Welding Department to enable them to perform their duties effectively.